Predictive Performance of Placental Protein 13 for Screening Preeclampsia in the First Trimester: A Systematic Review and Meta-Analysis - Wu, Yifan; Liu, Yang; Ding, Yiling (Frontiers in Medicine, 2021)
Preeclampsia is a pregnancy-specific syndrome that affects the maternal and neonatal mortality. There are several serum biomarkers which be used for prediction of preeclampsia. Among those proteins, PP13 has received progressively more interests during recent studies. It is notable that the decrease in PP13 expression is almost one of the earliest signs for the development of preeclampsia and has showed its predictive performance for preeclampsia. In this meta-analysis, we collected total 17 observational studies with 40474 pregnant women. The overall sensitivity of PP13 to predict the preeclampsia was 0.62 (95%CI = 0.49-0.74), the specificity was 0.84 (95%CI =0.81-0.86), and the diagnostic odds ratio was 9 (95%CI =5-15). The AUC for SROC was 0.84. Then we chose the early-onset preeclampsia as subgroup. The sensitivity of early-onset subgroup was 0.63 (95%CI =0.58-0.76), the specificity was 0.85 (95%CI =0.82-0.88), and the diagnostic odds ratio was 10 (95%CI=6-18). The findings of our meta-analysis suggested that PP13 might be an effective serum biomarker for predictive screening of preeclampsia. Nonetheless, large prospective cohort studies and randomized controlled trails are expected to uncover its application in clinical practice. The heterogeneity of original trails may limit the clinical application of PP13.